Psychometric properties of the Hospital Anxiety and Depression Scale (HADS) and associated factors of emotional distress among Moroccan cancer patients (Bangladesh Journal of Medical Science, 2026)
Psychological distress remains underdiagnosed in oncology settings across Low- and Middle-Income Countries, where transcultural validation of screening instruments and identification of treatment-specific predictors are critical for integrated psychosocial care. This cross-sectional study aimed to validate the Hospital Anxiety and Depression Scale (HADS) in a Moroccan oncological population and to examine the differential associations of anxiety and depression with sociodemographic, clinical, and treatmentrelated variables. Conducted at the Institut National d’Oncologie in Rabat, the study enrolled a consecutive non-probability sample of adult patients aged 18 to 60 years with histologically confirmed cancer. Psychological distress was assessed using the 14-item HADS, and the psychometric structure was explored via principal component analysis with Varimax rotation, while internal consistency was evaluated using Cronbach’s alpha; bivariate associations were examined through Spearman’s rank correlation, and multivariate associations with treatment type were modeled via multiple linear regression. The HADS demonstrated excellent sampling adequacy (Kaiser-Meyer-Olkin = 0.897) and a significant Bartlett’s test of sphericity (χ² = 725.68, p < 0.001), with principal component analysis confirming a robust two-factor structure accounting for 58.06% of total variance and excellent internal consistency (Cronbach’s α = 0.919). Although anxiety and depression were moderately-to-strongly correlated (r = 0.509, p < 0.01), only anxiety exhibited significant associations with diagnostic type (r = 0.201, p < 0.05) and treatment modality (r = 0.284, p < 0.01); multiple regression further identified anxiety as the sole significant predictor of treatment type (β = 0.239, p = 0.037), whereas depression showed no significant association (β = –0.040, p = 0.727). Additionally, female patients were significantly younger and had lower educational attainment, with education level positively correlated with insurance coverage (r = 0.263, p < 0.01), highlighting socioeconomic gradients in access to care. These findings establish the HADS as a valid and reliable instrument for screening psychological distress in Moroccan oncology patients and reveal a critical dissociation between anxiety and depression: anxiety emerges as a situational, treatment-sensitive marker responsive to therapeutic transitions, whereas depression appears more endogenous and independent of therapeutic modality. Consequently, the results support the implementation of differentiated, stepped-care psychosocial screening protocols that specifically target anxiety during treatment transitions, while underscoring the urgent need for equity-oriented policies addressing socioeconomic determinants of access to oncological care in resource-limited settings.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 953-962